Pengaruh Penerapan Model Direct Instruction Berbasis Video Animasi Terhadap Hasil Belajar IPAS Siswa di SDN 2 Tekorejo - Rizky Tedy Pratama; Jumroh; Noviati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the application of the direct instruction model based on animated videos on the learning outcomes of social studies students at SDN 2 Tekorejo. This research uses an experimental method, namely Quasi Experimental. With the form of Pretest – Posttest design. The sample in this study of 40 students in classes VA and VB, was taken from the Nonprobability Sampling technique. Based on the hypothesis test conducted by this researcher using the t-test of two independent samples (Independent sample t-test) obtained the result of ttable which is 4.078 and ttable value = 1.686 with α = 0.05 and df = 38, then ttable ≥ ttable so that HO is rejected. From the hypothesis test data, it can be concluded that there is an influence in the application of the direct instruction model based on animated videos on the learning outcomes of social studies students at SDN 2 Tekorejo.